2022
DOI: 10.1002/lno.12006
|View full text |Cite
|
Sign up to set email alerts
|

An intense precipitation event causes a temperate forested drainage network to shift from N2O source to sink

Abstract: Nitrous oxide (N2O) evasion from streams and rivers is a significant, yet highly uncertain, flux in nitrogen cycle models. Most global estimates of lotic N2O emission assume that evasion rates are proportional to inorganic nitrogen inputs to a stream or river. However, many field studies do not detect relationships between lotic N2O evasion and dissolved nitrogen concentration, highlighting the need for better understanding of process‐based controls on this flux. This study reports 4‐yr time series of pN2O and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…Moreover, little is known about the interactive effects of land use and wastewater effluent inflows on riverine GHG fluxes, and whether land use is the overarching controlling factor. Under temperate climatic conditions, pronounced seasonality regulates the availability of nutrients and to some extent the O2 in lotic ecosystems, which are both key factors driving instream GHG production and gas exchange rates (Borges et al, 2018;Rocher-Ros et al, 2019;Herreid et al, 2021;Aho et al, 2022). Cold winter periods are generally characterized by low instream carbon and nitrogen processing, which results in nutrient accumulation (e.g., Herreid et al, 2021), while high instream C and N processing are characteristic of warm summer periods (e.g., Borges et al, 2018;Aho et al, 2021Aho et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, little is known about the interactive effects of land use and wastewater effluent inflows on riverine GHG fluxes, and whether land use is the overarching controlling factor. Under temperate climatic conditions, pronounced seasonality regulates the availability of nutrients and to some extent the O2 in lotic ecosystems, which are both key factors driving instream GHG production and gas exchange rates (Borges et al, 2018;Rocher-Ros et al, 2019;Herreid et al, 2021;Aho et al, 2022). Cold winter periods are generally characterized by low instream carbon and nitrogen processing, which results in nutrient accumulation (e.g., Herreid et al, 2021), while high instream C and N processing are characteristic of warm summer periods (e.g., Borges et al, 2018;Aho et al, 2021Aho et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Under temperate climatic conditions, pronounced seasonality regulates the availability of nutrients and to some extent the O2 in lotic ecosystems, which are both key factors driving instream GHG production and gas exchange rates (Borges et al, 2018;Rocher-Ros et al, 2019;Herreid et al, 2021;Aho et al, 2022). Cold winter periods are generally characterized by low instream carbon and nitrogen processing, which results in nutrient accumulation (e.g., Herreid et al, 2021), while high instream C and N processing are characteristic of warm summer periods (e.g., Borges et al, 2018;Aho et al, 2021Aho et al, , 2022. Seasonality in precipitation regulates discharge, whereby heavy precipitation events or snowmelt during spring result in high discharge events.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted in Europe estimated the nocturnal deficit at 39% . This demonstrates that rivers and streams may be important sources of CO 2 and other greenhouse gases, e.g., methane (CH 4 ) and nitrous oxide (N 2 O); however, high-frequency measurements of their concentrations are to date limited …”
Section: Exploring the Full Potential Of High-frequency Water Quality...mentioning
confidence: 76%
“… 138 This demonstrates that rivers and streams may be important sources of CO 2 and other greenhouse gases, e.g., methane (CH 4 ) and nitrous oxide (N 2 O); however, high-frequency measurements of their concentrations are to date limited. 139 . Moreover, these studies highlight a blind spot that arises when only discrete daytime measurements of CO 2 are made and show that diel cycles in autotrophic and heterotrophic processes in streams need further consideration, necessitating continuous high-frequency in situ monitoring.…”
Section: Exploring the Full Potential Of High-frequency Water Quality...mentioning
confidence: 99%
“…Expectations for increased frequency and intensity of heatwaves, floods, and storms are motivating research to investigate the consequences of these events for aquatic ecosystems. Aho et al (2022) measured nitrous oxide evasion from streams and observed large shifts associated with an intense storm and subsequent wet period. Changes in evasion were persistent, which reflects alterations to nitrogen cycling caused by the storm.…”
Section: The Transition From Theoretical To Empirical Sciencementioning
confidence: 99%